Information and competitiveness in trade (2010)
Provides information on the Single Electronic Window (SEW), an IT-based facilitation tool, designed by the Government of Trinidad and Tobago as a one-stop-shop which private stakeholders and approving government agencies can collaborate to process necessary permits and approvals. Looks at the initiative by the Caribbean Shipping Association (CSA) to develop and deploy an integrated Regional Maritime IT Platform that captures and disseminates timely, accurate and critical cargo, cruise and luxury yacht information for stakeholders.
Keywords: STATISTICAL DATA